An unusual location of the origin of an adenosine-sensitive atrial tachycardia: The lateral mitral annulus. Issue 2 (August 2021) - Nakamura, Kohki; Sasaki, Takehito; Minami, Kentaro; Kishi, Shohei; Take, Yutaka; Naito, Shigeto
Abstract: A 56-year-old woman underwent an electrophysiological study and radiofrequency catheter ablation of a narrow QRS tachycardia. Programmed atrial extrastimulation reproducibly induced the tachycardia. During the tachycardia, differential atrial overdrive pacing exhibited no ventriculoatrial (VA) linking, and ventricular overdrive pacing exhibited VA dissociation. Entrainment of the tachycardia with atrial overdrive pacing was not demonstrable because the tachycardia cycle length varied from 262 to 320 ms. An intravenous bolus of 5 mg of adenosine reproducibly terminated the tachycardia without atrioventricular (AV) block. Based on these findings, the clinical tachycardia was diagnosed as an adenosine-sensitive atrial tachycardia (AT). Activation mapping during the AT using the EnSite Precision system and Advisor HD Grid mapping catheter (Abbott, Minneapolis, MN, USA) exhibited a centrifugal pattern with the earliest activation along the lateral mitral annulus. A radiofrequency application at the earliest activation during the AT successfully terminated the AT. Adenosine-sensitive ATs generally originate from the vicinity of the AV node and tricuspid annulus. We present a case with an unusual location of the origin of an adenosine-sensitive AT, which was successfully ablated at the lateral mitral annulus. Since the AT was sensitive to adenosine, the AT substrate appeared to have been calcium channel-dependent tissue along the mitral annulus. <Learning objective: Adenosine-sensitive atrial tachycardias (ATs) generally originate from the right-sided atrioventricular (AV) annulus and are eliminated by ablation at the vicinity of the AV node, tricuspid annulus, proximal coronary sinus, and non-coronary sinus of Valsalva. This case report described a rare type of an adenosine-sensitive AT originating from the lateral mitral annulus. A radiofrequency application targeting the earliest activation on the activation map during the AT terminated the AT.>